The subgradient extragradient method for pseudomonotone equilibrium problems. (2nd April 2020) - Dadashi, Vahid; Iyiola, Olaniyi S.; Shehu, Yekini
ABSTRACT: In this paper, an improvement of the extragradient algorithm is considered for finding a solution of pseudo-monotone equilibrium problems in real Hilbert spaces. We replace the second minimization problem onto a closed convex set in the extragradient method, with a subgradient projection onto some constructible half-space and propose a new method of getting the step-size. A convergence theorem for the generated sequence is proved and applied for finding a solution of variational inequality problem.